Out-of-hospital cardiac arrest: 30-day survival and 1-year risk of anoxic brain damage or nursing home admission according to consciousness status at hospital arrival. (1st March 2020) - Sondergaard, Kathrine B.; Riddersholm, Signe; Wissenberg, Mads; Moller Hansen, Steen; Barcella, Carlo Alberto; Karlsson, Lena; Bundgaard, Kristian; Lippert, Freddy K.; Kjaergaard, Jesper; Gislason, Gunnar H.; Folke, Fredrik; Torp-Pedersen, Christian; et al.
Abstract: Aim: To investigate the association between consciousness status at hospital arrival and long-term outcomes in out-of-hospital cardiac arrest (OHCA) patients. Methods: OHCAs between 18–100 years of age were identified from the Danish Cardiac Arrest Registry during 2005–2014. Patients with return of spontaneous circulation (ROSC) or ongoing cardiopulmonary resuscitation (CPR) at hospital arrival were included. Thirty-day survival was evaluated using Kaplan-Meier estimates. Risk of anoxic brain damage or nursing home admission and return to work among 30-day survivors were evaluated using Aalen-Johansen estimates and cause-specific Cox regression. Results: Upon hospital arrival of 13, 953 OHCA patients, 776 (5.6%) had ROSC and were conscious (Glasgow Coma Score [GCS]>8), 5205 (37.3%) had ROSC, but were comatose (GCS ≤ 8), and 7972 (57.1%) had ongoing CPR. Thirty-day survival according to status at hospital arrival among patients that were conscious, comatose, or had ongoing CPR was 89.0% (95% confidence interval [CI] 86.8%–91.2%), 39.0% (95% CI 37.6%–40.3%), and 1.2% (95% CI 1.0%–1.4%), respectively. Among 30-day survivors, 1-year risks of new onset anoxic brain damage or nursing home admission according to consciousness status were 2.4% (95% CI 1.2%–3.6%), 12.9% (95% CI 11.4%–14.3%), and 19.4% (95% CI 11.3%–27.4%), respectively. Among 30-day working-age survivors, more than 65% in each group returned to work within 5 years. Conclusion: Consciousness status at hospital arrival was strongly associated with 30-day survival in OHCA patients. Among 30-day survivors, a minority was diagnosed with anoxic brain damage or admitted to a nursing home and the majority returned to work independent of consciousness status at hospital arrival.